Bridging Languages: Metacognitive Strategies for Improved Narrative Translation - Aqzhariady Khartha; Nur Wirawati; Marhamah; Muhammad Rifqi Syamsuddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aimed to enhance students' skills in translating narrative texts from English to Indonesian through metacognitive strategies among 10th-grade students at SMA Negeri 14 Gowa. Conducted as classroom action research (CAR) over two cycles, the study involved 36 students and utilized metacognitive strategies to foster self-regulated learning. Data were collected via observations, portfolios, formative assessments, and interviews, analyzed descriptively and qualitatively. Results showed significant improvements across six translation aspects: accuracy (16.67% to 66.67%), readability (19.44% to 72.22%), cultural relevance (13.89% to 61.11%), consistency (22.22% to 77.78%), grammar (16.67% to 69.44%), and completeness (25.00% to 83.33%). Metacognitive strategies enabled students to plan, monitor, and evaluate their translation processes, enhancing their contextual understanding, cultural adaptability, and analytical skills. The study underscores the effectiveness of metacognitive approaches in improving translation competence and promoting learner autonomy, with implications for integrating such strategies into language education to address global communication challenges.